Pulmonary tuberculosis risks and challenges - Mejbel Fatima Abdul Hussein; Aljanaby Israa Abduljabbar Jaloob; AL hadrawi Kais Khudhair; Aljanaby Ahmed Abduljabbar Jaloob (E3S Web of Conferences, 2023)
Pulmonary Tuberculosis (PTB) is an airborne bacterial infection that can be deadly if not treated. PTB is most common in developing countries, ecologically problematic, where it kills about 1 million people each year. Pulmonary tuberculosis is a dreaded disease that can have a devastating impact on its victims. Tuberculosis is a serious respiratory infection caused by the bacterium Mycobacterium tuberculosis. It commonly affects the lungs but can also affect other parts of the body, such as the kidney, spine and brain. This review article discusses the PTB risks and challenges word wide. The global burden of TB remains high, with approximately one-third of the world's population being infected with the bacterium. Overall, more needs to be done to improve the management of TB worldwide in order to ensure that no person is left to suffer from the devastating effects of this disease.